Analisis Numerik Pengaruh Suhu Tinggi Terhadap Momen Kapasitas Penampang Elemen Balok Beton Bertulang - Florisa Florisa; Reni Suryanita; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The heat during the fire will change the nominal moment capacity of reinforced concrete (RC) beam. The purpose of this study is to identify the nominal moment capacity of RC beam due to exposure of high temperatures with the heating temperatures of 500°C, 700°C, 800°C, and 1000°C. The duration of the heating time in each temperature is 0,5 hours, 1 hour, 1,5 hours, 2 hours, 3 hours, and 4 hours. In this study, the moment capacity was calculated by using the cross-section reduction method proposed in Eurocode EN 1992 1-2 (2004). The concrete strength and the yield strength of material used in this study was 35 MPa and 400 MPa, respectively. The results showed that the residual moment capacity of RC beam at temperature of 500°C was 95.835%, at temperature of 700°C was 82.255%, at temperature of 800°C was 71.238% , and at a temperature of 1000°C was 51.743% from the moment capacity of the normal concrete strength. Keywords : high-temperature, reinforced concrete beam, Isotherm 500°C, moment capacity.